RANCANG BANGUN ROBOT LINE FOLLOWER PEMADAM API BERBASIS MIKROKONTROLLER ATMEGA 16 - Rini Nuraini (FAKULTAS TEKNIK, 2020)
The fire area is not always in an easily accessible place, under certain conditions, there are times when it is not possible for humans to extinguish fires in the event of a fire, so certain smarter devices need to have the ability to detect and extinguish fires, namely Fire Extinguisher Robot. Robot Line Follower Fire Extinguisher designed by the author, works walking to find hotspots, if the sensor gets hot temperatures or hotspots, then the ic microcomtroller stops the dc motor, then another dc motor will be active to turn on the fan or fan. The method in this paper begins with designing a robot using the Proteus 8 simulator, making a robot, finally conducting a test and measurement. This study uses three dc motors, one dc motor to simulate the open lid or activate a fan or fan, two dc motorsto run the robot. The output of this robot is a line follower robot that serves to extinguish the fire